UPAYA PEMERINTAH MENINGKATKAN WISATAWAN TIONGKOK KE INDONESIA TAHUN 2017-2019 - Bintang Monica; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The development of the science of international relations is not only oriented to the socio-economic aspect but also the tourism sector, which is important to be considered as a potential contributor to the country's foreign exchange in the future. Efforts to increase the development of the tourism sector are needed because they are able to have a positive impact on a country. Tiongkok is the country that occupies the first position as a contributor to global tourism spending of up to 102 million USD. Indonesia-Tiongkok bilateral relations in the tourism sector aim to increase foreign tourists. This study uses a qualitative descriptive method, with data collection techniques through literature studies sourced from several books, journals, articles, internet, thesis. This research uses a globalist perspective and international cooperation theory. The results show that the Indonesian government is trying to increase Chinese tourists by providing visa-free visits, holding tourism promotion events, deregulating the cabotage principle for foreign cruises, removing the Clearance Approval for Indonesia Territory (CAIT) provisions, opening Indonesian and Chinese airline, establishing cooperation in the Indonesia Tiongkok Chamber of Commerce (INACHAM) organization, carrying out promotional activities through Astro TV, National Geographic Australia, Channel News Asia, Ali Trip, Weibo, We Chat, tripadvisor, and Traveloka, as well as pairing the Wonderful Indonesia brand in Shanghai and Beijing. Indonesia also sends Chinese teachers to increase the number of Mandarin language users and cultural exchanges, which will increase the number of Chinese tourists. Keywords: Chinese tourists, government, Indonesia, tourism.